ISOLASI DAN IDENTIFIKASI SENYAWA IMUNOMODULATOR UMBI SARANG SEMUT (Myrmecodia pendens MERR & PERRY) - , Maria Ulfah, S.Farm., Apt.; , Dr. rer. nat. Triana Hertiani, M.Si., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Immunomodulator is an agent that helps to maintain immune system. Ants plant belongs to rubiaceae family that is widely used by Indonesian people as part of traditional medicine for various diseases. Wide therapeutic effects suggest its immunomodulatory activity as part of healing properties. The purpose of this study was to investigate the immunomodulatory activity and to identify the active compound of the ants plant (Myrmecodia pendens Merr & Perry) by an in vitro technique. Dried powders of ant plant were extracted by using maceration method with ethanol 95%. Extract obtained was then fractioned by liquid-liquid partition using n-hexane, ethyl acetate and water, excessively. Extracts and fractions were tested against lymphocyte proliferation and macrophage phagocytosis. Lymphocytes and macrophages were isolated from Balb/c male mice 2 months old. The most active fraction was further fractionated by using two different method, i.e: column chromatography (sephadex LH20, metanol) and VLC (silica gel, increasing polarity of solvent started from n-hexane followed by ethyl acetate and ended by methanol). The fractions yielded were further tested by lymphocyte proliferation assay using MTT assay. Each fractions was analysed the total phenolic contents by using Folin-Ciocalteau method. Active compound was identified by GC-MS, UV-Vis spectroscopy, IR and 1H-NMR. The study result showed that phenolic compounds played a role in lymphocyte proliferation induction. Fraction 7 yielded from VLC (ethyl acetatemethanol